Development of portable linear positioning table for drilling machine - Ab Wahab, Norfariza; Abd Rahim, Abdul Fattah; Nordin, Abd Khahar; Bidin, Basri; Ibrahim, Mohd Azimin; Zahari, Madiha; Abd Mutalib, Nurliyana (Asian Research Publishing Network (ARPN), 2018)
Drilling operation is an operation which produces holes by bringing a rotating cutter into contact with the workpiece. Drilling operation is commonly done in drill press, however some of the time; it is done on mills or lathes. Holding parts to be drilled is one of major problems faced by the students. If the material has many holes to be drilled, then the procedure adopted is by marking out with a center punch, setting on the machine (Drill Press Machine), and holding the workpiece. This is time consuming and dangerous as the students need to hold the material they throughout the drilling process. This project presents an innovative linear sliding table to ease the operator during drilling process. In addition, the clamping system will also be provided for better rigidity and less movement of the workpiece during the drilling process. Some toggle clamps are fixed on the table to hold the position of the part securely from moving throughout the machining cycle. Furthermore, this project focuses on the execution of the drilling process in one single clamping. A simple and economic design is proposed.